A Feature Clustering and Multi-Object Alignment Framework for Detailed Vehicle Recognition. - Mariano, Vladimir Y. (Philippine Computing Journal)
We present a novel method for detailed recognition of vehicle images. Given the output of a general image retrieval system, an iterative scheme uses multi-object feature clustering and image alignment to reduce the number of images in the search space. In each iteration, the reduced search space becomes more homogeneous and better aligned. The reduction scheme uses the cluster membership of object features to decide which objects will be pruned from the search space. The method is applied to recognition of recurring vehicles in a street scene.